Chapter Is Three better than Two? A Study on EEG Activity and Imagination Abilities in 2D vs 3D Stimuli - Lucchiari, Claudio (Proceedings e report, 2018)
Real and virtual are often considered terms in reciprocal opposition, but the boundaries between the two are blurred. The main goal of our study consists in answering the question whether the presence of a third dimension (3D) is a fundamental step of the virtual toward the real world, and if it causes some difference in the neural activity of the spectator [8]. Also, the possibility to consider real what is virtual will be discussed [6, 7].